PENGARUH PENGELOLAAN KELAS TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI PADA KELASVIII DI SMP N 2 BENAI KECAMATAN BENAI KABUPATEN KUANTAN SINGING - Nurma Winda; Sarmidin Sarmidin; Sopiatun Nahwiyah (Universitas Islam Kuantan Singingi, 2020)
Proficiency in classroom management by teachers becomes something that is very necessary, because with this more effective teaching will be realized and will lead to positive attitudes in students can be developed. In June, the observation that the writer met at SMP N 2 Benai the teacher has not been able to minimize the behavior of students in class properly,such as: students often make noise, talk when the teacher explains, copying students to students who are smart in class when given assignments or homework at home, and lack of effort from some students to get high gradesThe purpose of this study was to determine the effect of classroom management on student learning motivation in Islamic education and character education subjects at SMP N 2 Benai.This type of research used in this research is quantitative research is one type of research whose specifications are systematic, planned, and clearly structured from the beginning to the design of the research. The subjects of this study were all students of class VIII, amounting to 38 students and 1 teacher. Data collection techniques in this study used observation, questionnaires, interviews, and documentation. While the data analysis is to use a simple linear regression analysis that serves to determine whether there is an influence of classroom management on student motivation in SMP N 2 Benai.Based on the results of regression analysis by looking at the significance value (sig.). if the significance value (sig.) is smaller (0.160) <than the probability (0.05) it means that there is an influence of Class Management (X) on Learning Motivation (Y) and vice versa, if the significance value (sig.) is greater (0.160) )> of probability (0.05) implies that there is noeffect of Class Management (X) on Learning Motivation (Y). The magnitude of the coefficientof determination (R Square) of 0.063 is 6.3% while the remaining 93.7% is influenced by other variables not examined in this study. the conclusion is because the sig value of this study is greater (0.160) than the probability value (0.05), it can be concluded that there is no influence of classroom management on learning motivation.